Legal Regulation of E-Ñommerce - Leonidovna Burova, Inna; Sergeyevna Lavrentieva, Maria; Romanovna Lenkovskaya, Renata; Anatolevich Malcev, Vitalij; Nikolaevich Kuleshov, Georgij (International Journal of Engineering and Technology, 2018)
This article analyzes the current state of electronic commerce in Russian Federation and highlights good foreign practices in this area. The conceptual framework and Internet transactions are also assessed. The terminological imprecisions and adoption of foreign law definitions and principles of transactions are revealed. Amendments and additions to the Russian e-commerce legislation are proposed.Â Â